2021
DOI: 10.6018/red.450711
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del proceso metodológico en programas de educación superior en modalidad virtual

Abstract: El propósito de este artículo consiste en identificar las características metodológicas de los programas virtuales de educación superior en instituciones colombianas. Este objetivo se deriva de la carencia de lineamientos acerca de cómo implementar procesos de educación virtual a nivel de pregrado y posgrado en un país en vía de desarrollo como Colombia. Para lograr este objetivo, se llevó a cabo una investigación de enfoque cualitativo en una muestra a propósito de 10 instituciones de educación superior en Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
0
4
0
8
Order By: Relevance
“…Online teaching requires specific preparation of the teacher who, in addition to handling virtual tools and ICT, must develop a pedagogical model that is different from face-to-face teaching (Díaz-Guillen et al, 2021). The outbreak of the pandemic made it necessary to adopt rapid measures in a short-term time horizon, which also introduced unavoidable errors in the approach, which must be different for virtual teaching.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Online teaching requires specific preparation of the teacher who, in addition to handling virtual tools and ICT, must develop a pedagogical model that is different from face-to-face teaching (Díaz-Guillen et al, 2021). The outbreak of the pandemic made it necessary to adopt rapid measures in a short-term time horizon, which also introduced unavoidable errors in the approach, which must be different for virtual teaching.…”
Section: Discussionmentioning
confidence: 99%
“…The move to online teaching, forced by the circumstances arising from the pandemic, obviated the lengthy processes of training, redesign of subjects and infrastructures required by e-learning (González-Calvo et al, 2020). The methodological characteristics of virtual education differ from face-to-face education, so institutions must approach both modalities with different pedagogical strategies (Díaz-Guillen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Cáceres Pinaloza has argued that the population is used to in-person classes and the shift away from this format causes fear and frustration among students and teachers (Cáceres, 2020). Other researchers (Colomina Álvarez et al, 2005), (Jordan et al, 2021) have found that education in many countries is not working as well as usual due to the emergence of a digital divide in terms of access to the internet and digital media, even though higher education has a recent history of undergoing digital transformation and facilitating access to techno-pedagogy (Díaz Guillen et al, 2021) Studies on academic engagement at universities have shown commitment and outcomes can be sustained as challenges arise (Horstmanshof & Zimitat, 2007), insofar as responsible decision making can overcome environmental and motivational problems, (McInnis, 2001) including the online learning necessitated by the Covid-19 pandemic. Governments around the world have closed schools and universities, resulting in the large-scale assumption of commitments to technology by educators and educated (Al-Karaki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudios se publicaron en el último año referentes a la educación en tiempos de la pandemia Covid-19. Cáceres-Piñaloza (2020) argumenta la importancia de los espacios afectivos; Kem-Mekah (2020), Jordan y col. (2020), Lin y Reigeluth (2020) y Hernández-Ramos, Martínez-Abad y Sánchez-Prieto (2021) transmiten sus experiencias a partir de la interactividad con los recursos educativos digitales; otras investigaciones establecen los desafíos educativos actuales ante la Covid-19 (BAPTISTA LUCIO; ALMAZÁN ZIMERMAN y LOEZA ALTAMIRANO, 2020; MIGUEL, 2020; FLO-RES NESSI; MELÉNDEZ MORA y BAPTISTA MONTERO, 2020; VELÁSQUEZ, 2020; JIMÉNEZ y RUIZ, 2021) mientras que diversos autores exponen las principales preocupaciones motivacionales de los matriculados en cursos virtuales (DÍAZ GUILLEN y col., 2018;OJEDA;ORTEGA y BOOM, 2020;VALDIVIESO;BURBANO y BURBANO, 2020;GONZÁLEZ, 2020). Coherente con estas últimas investigaciones, se aborda la relación entre el rendimiento académico, engagement y el estrés causado por el confinamiento que viven la mayoría de las personas (ÁLVAREZ-HERRERO y HERNÁN- DEZ ORTEGA, 2020;HERNÁNDEZ, 2020;MAHDY, 2020;VALDIVIESO;BURBANO y BURBANO, 2020;SANTIAGO y col., 2021).…”
Section: Abstract 1 Introducciónunclassified